(untitled) (Research, Society and Development, 2020)
The city of Redenção-PA is considered a hub in the Araguaia region. Because it is the second largest linked to the 12th Regional Health Center, the municipality, in addition to meeting its demand for health care, also receives many patients from the other 14 municipalities in the region. Redenção-PA has twelve Basic Health Units (UBS), with a Family Health Strategy in place, six of which formed the research field of this study. The population’s lack of concern in relation to environmental issues that cause diseases and the lack of knowledge about the possibilities of coping with these diseases, characterized as environmental, are the focus of this work. The research came to list the five preventable environmental diseases, most frequent in the Family Health Strategies and the environmental impacts that cause them. The research was qualitative and quantitative, with statistical treatment of the collected results. The actions for the development of the research took place through meetings with: conversation circles, application of the questionnaire, group dynamics and elaboration of the Action Plan. The research evidenced the need to enhance the actions of Primary Health Care since the diseases identified as having the highest incidence are diseases considered to be environmental and with a great possibility of prevention, control and cure. It is noteworthy that investing in prevention is decisive not only to guarantee the quality of life but also to avoid hospitalization and the consequent high costs for public health.